Alisol B 23-Acetate Ameliorates Lipopolysaccharide-Induced Intestinal Barrier Dysfunction by Inhibiting TLR4-NOX1/ROS Signaling Pathway in Caco-2 Cells - Xia, Fan; Li, Yuxin; Deng, Lijun; Ren, Ruxia; Ge, Bingchen; Liao, Ziqiong; Xiang, Shijian; Zhou, Benjie (Frontiers in Pharmacology, 2022)
Alisol B 23-Acetate (AB23A) is a naturally occurring triterpenoid, which can be indicated in the rhizome of medicinal and dietary plants from Alisma species. Previous studies have demonstrated that AB23A could inhibit intestinal permeability by regulating tight junction (TJ)-related proteins. Even so, the AB23A protective mechanism against intestinal barrier dysfunction remains poorly understood. This investigation seeks to evaluate the AB23A protective effects on intestinal barrier dysfunction and determine the mechanisms for restoring intestinal barrier dysfunction in LPS-stimulated Caco-2 monolayers. According to our findings, AB23A attenuated the inflammation by reducing pro-inflammatory cytokines production like IL-6, TNF-α, IL-1β, and prevented the paracellular permeability by inhibiting the disruption of TJ in LPS-induced Caco-2 monolayers after treated with LPS. AB23A also inhibited LPS-induced TLR4, NOX1 overexpression and subsequent ROS generation in Caco-2 monolayers. Transfected with NOX1-specific shRNA diminished the up-regulating AB23A effect on ZO-1 and occludin expression. Moreover, transfected with shRNA of TLR4 not only enhanced ZO-1 and occludin expression but attenuated NOX1 expression and ROS generation. Therefore, AB23A ameliorates LPS-induced intestinal barrier dysfunction by inhibiting TLR4-NOX1/ROS signaling pathway in Caco-2 monolayers, suggesting that AB23A may have positive impact on maintaining the intestinal barrier's integrity.